PENGEMBANGAN MEDIA PEMBELAJARAN LITERASI TOLERANSI BERAGAMA BERBASIS ANDROID - Supriyaddin; Idhar; Rahman, Arif; Prayudi, Andi; Juliadin (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to develop an Android-based learning media for religious tolerance literacy among junior high school students. The researcher’s initial observation at SMP Negeri 1 Dompu revealed that students come from diverse backgrounds, including economic, social, and religious differences. Although the majority of students are Muslim, there are also non-Muslim students. Therefore, Islamic religious education at SMP Negeri 1 Dompu is required to consistently instill values of interreligious tolerance.The method used is Research and Development (R&D) with the 4-D model (Define, Design, Develop, Disseminate). The research subjects were 30 seventh-grade students of SMP Negeri 1 Dompu. Validation results from material experts and media experts indicated a “very valid” category, meaning the media is feasible for use. The practicality test involving teachers and students obtained a “very practical” category, showing that the media is easy to use and beneficial for learning. Effectiveness testing through pre-test and post-test showed an average improvement of 17 points, proving that the media is effective in improving students’ understanding of religious tolerance literacy. Teacher and student responses were also very positive, with teachers feeling assisted in delivering material and students becoming more motivated and active in learning. Thus, this Android-based learning media can serve as an innovative solution in instilling the values of religious tolerance in schools.